Collective Mind in Organizations: Heedful Interrelating on Flight Decks - Weick, Karl E.; Roberts, Karlene H. (Administrative Science Quarterly, 1993)
We acknowledge with deep gratitude, generous and extensive help with previous versions of this manuscript from Sue Ashford, Michael Cohen, Dan Denison, Jane Dutton, Les Gasser, Joel Kahn, Rod Kramer, Peter Manning, Dave Meader, Debra Meyerson, Walter Nord, Linda Pike, Joe Porac, Bob Quinn, Lance Sandelands, Paul Schaffner, Howard Schwartz, Kathie Sutcliffe, Bob Sutton, Diane Vaughan, Jim Walsh, Rod White, Mayer Zald, and the anonymous reviewers for Administrative Science Quarterly.